(untitled) (Ustozlar uchun, 2026)
This thesis investigates the verbs of intensity in English and Uzbek languages, focusing on their structural, semantic, and functional characteristics. Verbs of intensity express varying degrees of action, state, or process and play a crucial role in conveying nuance, emphasis, and emotional or cognitive force within communication. A comparative analysis of these verbs in English and Uzbek reveals how linguistic, morphological, and cultural factors influence the expression of intensity in different languages. The research examines both grammatical and semantic properties of intensity verbs, including their derivational patterns, aspectual features, syntactic behavior, and pragmatic functions. In English, intensity is often conveyed through auxiliary verbs, adverbial modification, phrasal constructions, or semantic gradation (e.g., strengthen, intensify, heighten), whereas in Uzbek, agglutinative morphology, verb affixation, and context-dependent markers play a central role in expressing intensification. This study also considers the interaction between verb semantics and sentence structure, showing how intensity verbs function in relation to arguments, mood, and aspect to enhance meaning. Using descriptive, analytical, and contrastive methods, the thesis identifies both convergences and divergences in the use of intensity verbs across the two languages. It highlights universal linguistic principles underlying the expression of intensity while illustrating language-specific strategies shaped by morphology, syntax, and cultural context.